Literature Review: Pharmacological Activity and Characteristics of Red Onion (Allium cepa L.) - Arista Wahyuningsih; Shinta Mayasari; Iski Weni Pebriarti; Sepbrilla Ananda Kusriadi (Indonesian Pharmacopeia Journal, 2025)
Shallot skin (Allium cepa L.) is a household waste that is still rarely utilized, even though it contains secondary metabolites such as flavonoids, anthocyanins, saponins, tannins, and other phenolic compounds that have pharmacological potential, especially as antioxidants and antibacterials. This study evaluates shallot skin's specific and non-specific pharmacognosy parameters through literature studies. Specific parameters include organoleptic, microscopic tests, and identifying active compound content using TLC, while non-specific parameters include water, ash, and contamination. The literature search method was done through Google Scholar, PubMed, and ScienceDirect, using the criteria of articles from 2015 to 2025. The study results indicate that flavonoid content, especially quercetin, contributes significantly to the antioxidant and anti-inflammatory effects. Shallot skin also shows effective antibacterial and antimicrobial activity against pathogenic strains such as Staphylococcus aureus, Escherichia coli, and Salmonella typhi. In addition, the mechanism of inhibition of α-amylase and α-glucosidase enzymes shows potential as an antidiabetic agent. Anticancer activity is supported by the active compounds' ability to induce apoptosis and inhibit cancer cell proliferation. With its abundant bioactive compound profile, shallot skin has the potential to be developed.